ACE2: from protection of liver disease to propagation of COVID-19. Issue 23 (11th December 2020) - Warner, Fiona J.; Rajapaksha, Harinda; Shackel, Nicholas; Herath, Chandana B.
Abstract: Twenty years ago, the discovery of angiotensin-converting enzyme 2 (ACE2) was an important breakthrough dramatically enhancing our understanding of the renin–angiotensin system (RAS). The classical RAS is driven by its key enzyme ACE and is pivotal in the regulation of blood pressure and fluid homeostasis. More recently, it has been recognised that the protective RAS regulated by ACE2 counterbalances many of the deleterious effects of the classical RAS. Studies in murine models demonstrated that manipulating the protective RAS can dramatically alter many diseases including liver disease. Liver-specific overexpression of ACE2 in mice with liver fibrosis has proved to be highly effective in antagonising liver injury and fibrosis progression. Importantly, despite its highly protective role in disease pathogenesis, ACE2 is hijacked by SARS-CoV-2 as a cellular receptor to gain entry to alveolar epithelial cells, causing COVID-19, a severe respiratory disease in humans. COVID-19 is frequently life-threatening especially in elderly or people with other medical conditions. As an unprecedented number of COVID-19 patients have been affected globally, there is an urgent need to discover novel therapeutics targeting the interaction between the SARS-CoV-2 spike protein and ACE2. Understanding the role of ACE2 in physiology, pathobiology and as a cellular receptor for SARS-CoV-2 infection provides insight into potential new therapeutic strategies aiming to prevent SARS-CoV-2 infection related tissue injury. This review outlines the role of the RAS with a strong focus on ACE2-driven protective RAS in liver disease and provides therapeutic approaches to develop strategies to prevent SARS-CoV-2 infection in humans.